Komunikasi Pemasaran Program CSR "Pertamina Sehati" 2007-2008 - Irene Irawati; Sehti Nurhayati (Marcommers : Jurnal Marketing Communication and Advertising, 2008)
Marketing communications is a uer!!important aspect in coinmunicoti'rig, introducing grid i, !forming the product. Marketing communications is not only used for tangible products but alsofor intangible products that implement the corporate social responsibility(CSR). Pertaininaoccordisoneqf Pertainino^;CSRprogromsin theheolthjield. !PertaininaSehati' require marketing communications to be able to introduce on try'ormtheprogr"in wasogoodoneaccordPertaminatosogiet!I that become the targetqftheprogrom andtLiidercommt, nity. Mixqfcommunicotion orthecommunication tools used such OS aduerti'sing, media, to o60ue the line: aduerto, 'mis und public service aduertisements and the media below the line: exhibits, brochures, banners and banners; public relations use euent, news, talk shows, reports annual, Pertominos CSR profile book, and inagarr'ne companies.